The Relationship of Culture Media Composition and Chemical Composition on Spirulina sp for Metal Ion Adsorbent - Hilda Zulkifli; Zazili Hanafiah; Didi Jasantri; Aldes Lesbani (Sriwijaya Journal of Environment, 2017)
The analysis relationship of Spirulina sp medium with chemical composition has been conducted. Chemical analysis was performed using X-Ray Fluorescence analysis. Furthermore, potention of Spirulina sp as adsorbent of metal ions was analyzed using FTIR spectroscopy. The results showed that metals such as Zn, Fe, Mn, Ca, Cu, and Mo were mainly metals in Spirulina sp. These metals were not correlated with cultivated medium of Spirulina sp. Analysis of potention Spirulina sp as metal ions adsorbent showed that Spirulina sp has functional groups –C=O and –OH as ligand. Intercation of metal ions Cu(II) and Cr(III) with Spirulina sp indicated that metal ions bond to –C=O functional group.Keywords: Spirulina sp, media composition, chemical content, metal ion, adsorptionAbstrak (Indonesian): Telah dilakukan analisis hubungan komposisi media Spirulina sp dengan kandungan kimia yang dimilikinya. Analisis kandungan kimia dilakukan dengan X-Ray Fluorescence. Selanjutnya potensi Spirulina sp sebagai adsorben dalam mengikat ion-ion logam dianalisis menggunakan spektroskopi FTIR. Hasil penelitian menunjukkan bahwa logam Zn, Fe, Mn, Ca, Cu, dan Mo merupakan logam utama yang terkandung dalam Spirulina sp. Logam-logam tersebut diasumsikan tidak berasal dari medium tumbuh Spirulina sp. Analisis terhadap potensi Spirulina sp sebagai adsorben logam berat menunjukkan bahwa Spirulina sp memiliki gugus fungsional -C=O dan –OH yang potensial sebagai ligan. Interaksi ion logam Cu(II) dan Cr(III) dengan Spirulina sp menunjukkan bahwa ion logam terikat pada gugus –C=O.Kata kunci: Spirulina sp, komposisi media, kandungan kimia, ion logam, adsorpsi